Implementation of Bridge Watchkeeping to Avoid Collision Hazards on the MV. Tanto Bersinar 1: Pelaksanaan Dinas Jaga Anjungan untuk Menghindari Bahaya Tubrukan di MV. Tanto Subur 1 - Nurmala, Eka; Hartati, Diah Vitaloka; Jamil, T. M.; Hermanto, Fazri; Munziri, Al (ALTAIR: Jurnal Transportasi dan Bahari, 2024)
The role of sea transportation is crucial, particularly in the context of merchant shipping, as it can transport large loads efficiently. Sea-watch duties require significant concentration, precision, and high responsibility when sailing. Skilled sailors must be capable of making sound decisions to ensure the ship’s safety. Unfortunately, many accidents occur on board due to negligence during watch duties. This study employs a qualitative approach, with data presented through descriptive analysis. The findings of this research include: 1) efforts to improve watch discipline on the bridge; 2) the implementation of watch duties when entering narrow shipping lanes, highlighting what watch officers must do to prevent collisions; and 3) an examination of the reasons behind watch officers’ negligence concerning navigational instruments.